Pendekatan Kecerdasan Majemuk Dalam Pembelajaran Agama Islam - Mahfud, Muhammad; Rudianto, Rahmat (Program Studi Pendidikan Agama Islam, 2021)
Learning innovation is really needed in learning considering the intelligence possessed by a child is very diverse. This study wants to describe the religious learning innovation program carried out by Al-Azhar Gresik High School with a multiple intelligence approach. The research method used is qualitative research with a phenomenological-anthropological approach with data collection techniques in the form of structured interviews, participatory observation and documentation and data analysis used is descriptive analysis of Miles and Huberman. The results showed that innovation was carried out in five stages, namely introduction, persuasion, decision, implementation, and confirmation. The implementation of this innovation is carried out by means of a strategic plan, act, and evaluation.